1988
DOI: 10.1007/bf02544516
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transesterification and mass spectrometric approach to seed oil analysis

Abstract: Fatty acid composition of seed oil is determined in less than one hr using a quantitative one‐vial technique. The method of analysis requires alcoholic solutions of sodium methoxide mild enough for epoxy and polyunsaturated oils. Separation and characterization of component fatty acids were accomplished by high resolution gas chromatography‐mass spectrometry. Using this method,Vernonia galamensis seed oil is shown to contain 79–80% vernolic (cis‐12,13‐epoxy‐cis‐9‐octadecenoic) acid.Amaranthus cruentus, a West … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 4 publications
1
30
0
Order By: Relevance
“…11 Our rationale for carrying out base catalysis was to create milder reaction conditions so as to preserve the end groups of the parent polymer. Table 1 shows the relationship between the concentration of the sodium methoxide and the size of the resulting oligomers.…”
Section: Base-catalyzed Transesterificationmentioning
confidence: 99%
“…11 Our rationale for carrying out base catalysis was to create milder reaction conditions so as to preserve the end groups of the parent polymer. Table 1 shows the relationship between the concentration of the sodium methoxide and the size of the resulting oligomers.…”
Section: Base-catalyzed Transesterificationmentioning
confidence: 99%
“…Also, the base-catalyzed methanolysis (14) of the oil resulted only in transesterification to give epoxidized methyl ester. Consequently, we were interested in studying the effect of a nucleophilic agent such as LAH on the epoxy functionality.…”
mentioning
confidence: 99%
“…The products from this reaction could constitute potential intermediates in the synthesis of oleochemicals from Vernonia galamensis seed oil, since it has been recognized as a potential oil seed crop (11,12). The initial interest was due to the unique fatty acid composition of its seed oil, which contains epoxidized triacylglycerols, of which trivernolin has been shown to be the major triacylglycerol (13,14).Previous work in our laboratory indicated that the epoxy functionality in VO was reactive toward nucleophilic reagents only under acidic conditions (12), whereas aminolysis (15) of the oil gave epoxy-containing amides with no indication of epoxy opening. Also, the base-catalyzed methanolysis (14) of the oil resulted only in transesterification to give epoxidized methyl ester.…”
mentioning
confidence: 99%
“…Vernolic acid offers potential application in the formulation of additives, coatings, and lubricant additives. Vernonia oil has become a unique renewable candidate for industrial feedstock due to its use as raw material and its potential derivatization into value-added products [1,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Our group have recently reported the synthesis of epoxy fatty acid esters of cassava starch by reacting cassava starch with vernonia oil methyl ester (epoxy ester) using 1-butyl-3-methylimidazolium hexafluorophosphate, 6 ] ionic liquid (IL) as a reaction medium and DMSO as co-solvent [1]. Similarly we have also reported the successful preparation of epoxy fatty acid esters of cassava starch (starch vernolates) by reacting cassava starch with vernonia oil methyl ester using only 1-butyl-3-methylimidazolium chloride, [C 4 C 1 im]Cl, ionic liquid as a reaction medium and an inexpensive base such as pyridine as a catalyst [50].…”
Section: Introductionmentioning
confidence: 99%